In vivo plaque count of Streptococcus Mutans around orthodontic brackets bonded with two different adhesives - Al-Duliamy, Munad J (Journal of Baghdad College of Dentistry, 2014)
Background: The prevention of the enamel demineralization at the periphery of the brackets is a significant challenge to orthodontic professionals. The aim of this clinical study was to compare the Streptococcus mutants count in the plaque surrounding two orthodontic adhesive types, Fuji Ortho LC and Enlight (Ormco). Materials and methods: A total of 13 patients (7 male and 6 female) needing fixed orthodontic appliance therapy were participated. A split mouth technique was followed with appliances bonded by two orthodontic adhesive types, Fuji Ortho LC and Enlight (Ormco). Saliva was collected before placement of appliances (T0) and again at three weeks (T1) and six weeks (T2) after placement of appliances. Plaque was collected from areas adjacent to brackets and buccal tubes at three weeks (T1) and six weeks (T2) after placement of appliances. The numbers (colony-forming units) of Streptococcus mutans were determined with the side-specific modified Strip-Mutans. Results: No significant modification in the number of Streptococcus mutans CFU in saliva was observed at both time intervals (T1) and (T2) after placement of appliances. The number of Streptococcus mutans CFU in plaque at both time intervals (T1) and (T2) was statistically lower in sites adjacent to Fuji Ortho LC than in those adjacent to Enlight (Ormco) adhesive. Conclusion: plaque surround brackets and tubes bonded with Fuji Ortho LC adhesive harbor less Streptococcus mutans and this will aid in prevention of enamel demineralization.